2008
DOI: 10.1186/1471-2180-8-152
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Francisella tularensis in ticks and identification of their genotypes using multiple-locus variable-number tandem repeat analysis

Abstract: Background: Tularemia was reported in China over 50 years ago, however, many epidemical characteristics remain unclear. In the present study, the prevalence of Francisella tularensis in ticks was investigated during an epidemiological surveillance in China and then we measured their genetic diversity by conducting multiple-locus variable-number tandem repeat analysis (MLVA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…Third, multiple Francisella isolates, some identified as F. noatunensis, have been obtained from farmed and wild marine fish (reviewed in references 34, 45, and 46). Finally, Wolbachia persica endosymbionts and other Francisella-related organisms have been detected in ticks (47)(48)(49)(50)(51)(52)(53)(54). The distribution of these isolates is global, suggesting a worldwide distribution of Francisella organisms that inhabit fish, tick, and a variety of other environmental sources.…”
mentioning
confidence: 99%
“…Third, multiple Francisella isolates, some identified as F. noatunensis, have been obtained from farmed and wild marine fish (reviewed in references 34, 45, and 46). Finally, Wolbachia persica endosymbionts and other Francisella-related organisms have been detected in ticks (47)(48)(49)(50)(51)(52)(53)(54). The distribution of these isolates is global, suggesting a worldwide distribution of Francisella organisms that inhabit fish, tick, and a variety of other environmental sources.…”
mentioning
confidence: 99%
“…holarctica and MLVA disclosed genetic diversity. The study concluded that D. silvarum and I. persulatus might have a role in tularemia existence in China (Fang Zhang et al, 2008).…”
Section: Tularemiamentioning
confidence: 92%
“…Later, natural foci were reported to exist in Tibet, Xinjiang, and Gansu [12]. Tularemia cases have mainly been reported in 7 provinces/municipalities of Beijing, Heilongjiang, Inner Mongolia, Qinghai, Shandong, Tibet, and Xinjiang [10,12,13] (Table 1). In 1986, 31 cases of human infection were reported in a meat processing plant in Shandong province; since then, no further cases have been reported in China [12].…”
Section: Reviewmentioning
confidence: 99%
“…Holarctica ) in the natural environment, indicating these two tick species might have a role in tularemia existence in China [10]. Rodents and wild animals are its main source of infection, and infection generally occurs in spring and early summer.…”
Section: Reviewmentioning
confidence: 99%